American Workers' Experience with Socialism During the World Wars - John H. Pencavel (Institute of Labor Economics (IZA), 2025)
The operation of American labor markets during the two World Wars is described and the well-being of civilian workers during those years is assessed. These were periods when decentralized capitalism was replaced with a system of centralized direction and control that some would call socialism. The state's activities were those of a monopsonist - the dominant or, even, single buyer - in the markets for many goods and services. Why was decentralized capitalism discarded as a mechanism to allocate resources during these critical periods? How well did civilian workers fare during these years?
Keywords: J20; N32; P23; 330; World War; employment; wages; unionism; laissez faire; socialism